Does diversity make collaborative subsidies effective? ICT sector in Korea. Issue 1 (2nd January 2022) - Lee, Jeongwon; Hwang, Junseok; Kim, Hana
ABSTRACT: Research and development (R&D) collaboration becomes essential as technology becomes more complex, and technological change occurs at an unprecedented rate in high-tech sectors such as information and communication technologies (ICT). However, no concrete evidence exists on the benefits of collaboration diversity in terms of government support. Therefore, this study investigates whether a firm's innovation increases not only as R&D collaboration partners' diversity increases but also as firms engage in cross-sectoral R&D collaboration. Government subsidies for ICT firms that collaborate with other firms and research institutions at the same time have significantly positive effects on firm performance. Interestingly, cross-sectoral collaborations increase innovation activity. The results suggest that firm innovation can be efficiently achieved through R&D partner diversity, and the R&D subsidy scheme needs to focus on collaboration with diverse R&D partners with different knowledge to generate innovative outcomes.